2018
DOI: 10.1177/1087054718762486
|View full text |Cite
|
Sign up to set email alerts
|

Parental Emotion Regulation and Mentalization in Families of Children With ADHD

Abstract: Study findings highlight the importance of evaluating and addressing parental ER in interventions attempting to reduce coercive parenting. The findings also highlight the potential role of parental mentalization as a protective mechanism against hostile parenting in families of children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 72 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…Although recent research indicates the importance of mentalization in the ADHD field, both in empirical studies and in parenting interventions, only one study to date has investigated this issue in families of children with ADHD, showing that parental mentalization could act as a buffer against parental hostility (9). Recent research demonstrating the relationship between PRF and parents' capacity to regulate their own emotions in the caregiving context indicates the importance of the meaning parents apply to children's behaviors to determine the emotional/physiological level of arousal the parent experiences in reaction to them (9). Drawing upon these findings and upon studies showing more parenting and familial difficulties among parents of children with ADHD, the second aim of this study was to explore potential PRF impairments in parents of children with ADHD and to compare these impairments with those of a control group of parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although recent research indicates the importance of mentalization in the ADHD field, both in empirical studies and in parenting interventions, only one study to date has investigated this issue in families of children with ADHD, showing that parental mentalization could act as a buffer against parental hostility (9). Recent research demonstrating the relationship between PRF and parents' capacity to regulate their own emotions in the caregiving context indicates the importance of the meaning parents apply to children's behaviors to determine the emotional/physiological level of arousal the parent experiences in reaction to them (9). Drawing upon these findings and upon studies showing more parenting and familial difficulties among parents of children with ADHD, the second aim of this study was to explore potential PRF impairments in parents of children with ADHD and to compare these impairments with those of a control group of parents.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the demanding, moody and uncooperative behavior described among children with ADHD can represent a parenting challenge and has an impact on parental behavior and adjustment. On the other hand, parenting characteristics and difficulties may exacerbate children's behavioral difficulties and the course of the disorder (912).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it was shown that mothers with ADHD symptoms have difficulty setting limits and appropriate rules, leading to chaotic home environment and inconsistent discipline (Chen & Johnston, 2007; Mokrova, O'Brien, Calkins, & Keane, 2010). In addition, they were more negative, reactive, or even hostile and they could not respond appropriately to their child's needs for attention (Barkley, Guevremont, Anastopoulos, DuPaul, & Shelton, 1993; Ellis & Nigg, 2009; Gershy & Gray, 2020). Furthermore, it was demonstrated that although mothers with ADHD could find the same number of solutions for their child's behavior problems, the quality and organization was inferior compared to mothers without ADHD (Murray & Johnston, 2006).…”
Section: Introductionmentioning
confidence: 99%